Navigating Digital Literacies: an Exploration of Technical Students’ Critical Evaluation and Information-Seeking Behaviors in Informal English Language Learning - Safia BOUFARES & Fatiha HAMITOUCHE (Akofena)
Abstract: This study explores how first-year engineering students apply information and critical literacies to assess online materials while learning English informally through media, focusing on their evaluation of digital sources and their information-seeking and retrieval practices. The study is driven by New Literacies Theory and existing digital literacy frameworks in collecting survey data from 160 students about their critical literacy practices, information-seeking behaviors, choice of platforms, and strategies for evaluation. On the whole, the results provide a detail-rich nuanced image of the students' abilities. While the students are, in general, proficient at searching the internet, their evaluation of English-language resources leaned heavily on superficial criteria and frequently neglecting significant credibility indicators. Students favored information searches more on socially interactive multimedia-rich platforms than through traditional sources of an academic nature. These results challenge the assumption that students in technical fields are “digital natives” and thus familiar with digital literacies. They also provide insightful information for academics and educators, promoting the necessity for comprehensive literacy teaching strategies that take into account the unique difficulties students encounter when negotiating the intricate world of informal English language learning